PSXI-3 Tussock dynamics in pastures of BRS Zuri and BRS Quênia under rotational stocking. (7th December 2018) - Freitas, C; Ribeiro, K; Valote, P; Jaguaribe, T; Abreu, M; Sousa, M; Morenz, M; Gomide, C
Abstract: The objective of this study was to evaluate soil cover in P. maximum cultivars pastures through frequency and perimeter measurements of tussocks. The experiment was carried out at CNPGL, Coronel Pacheco, Minas Gerais, Brazil. Three subsequent grazing cycles with pastures from cultivars BRS Zuri and BRS Quenia, managed under rotational stocking with occupation and rest period of the paddocks of 3d and 21d, respectively, were evaluated. The design was the randomized blocks with 3 replicates of area, constituted by 8 paddocks of 830 m2, totalizing 48 paddocks. To measure the frequency and perimeter of tussocks, a 10 meters long nylon string with marks every one meter was used. At each point marked on the string, the occurrence of tussock, bare ground and weeds was recorded, totalizing 20 points evaluated per paddock; when tussocks were identified, its perimeter was measured using a metric tape. Data were analyzed using the SAS software, at 5% probability, and the means compared by the F test to cultivars and Tukey test to cultivar x cycle interaction There was a cultivar x cycle interaction for relative frequency of tussocks (P = 0.0156). In the comparison between cultivars, a higher frequency of tussocks for BRS Quenia (55.4%) compared to BRS Zuri (47.2%) was observed. The perimeter of tussocks varied according to the cultivar, with BRS Zuri showing tussocks perimeter of 1.32 m and BRS Quenia of 1.03 m. The difference found during the grazing cycles for the variables tested maybe related to a response from pasture conditioning to grazing, stimulating the tillering and increasing the frequency of the tussocks. The higher frequency of tussocks with smaller perimeters verified for BRS Quenia results in a better soil cover, observing that, on average, there was less than 50% of the bare ground or with weeds for this cultivar pastures.